Transformasi Pola Pemukiman Akibat Perluasan Kawasan Industri di Wilayah Ciwandan - Agus Rohman; Muhammad Fajrul Falah; Ajay Sutriyadi; Akrom Akrom (Pusat Riset dan Inovasi Nasional, 2025)
The transformation of settlement patterns in Ciwandan District, Cilegon City, is a consequence of massive industrial expansion over the past two decades. This change has resulted in the conversion of coastal agricultural land into high-density urban-industrial areas with heterogeneous settlement characteristics. This study aims to describe population dynamics, spatial structure changes, and their impact on the quality of life of the community. The approach used is descriptive qualitative with a literature review method. The findings indicate that the increase in population, particularly the working-age population, is accompanied by the growth of informal housing and pressure on basic infrastructure such as sanitation, clean water, and green open spaces. The imbalance between industrial growth and the provision of public services has created various social and ecological challenges. Therefore, there is a need for the integration of spatial planning policies, adaptive infrastructure development, and partnerships between the government, the community, and the industrial sector to create livable and sustainable residential areas.